Pengaruh Program Kualitas Pelayanan Online Terhadap Kepuasan Masyarakat Dinas Pencatatan dan Kependudukan Sipil Kota Bandar Lampung.: Keywords: Online Service Quality Program, Community Satisfaction - hardianpratama, reza; manan, mohammad athian (Balitbangda Provinsi Jambi, 2024)
Abstract The problem of public satisfaction with civil population registration administration agencies has the impact of inefficiency in making KTP, Family Cards, Birth Certificates and updating data on civil registration in the city of Bandar Lampung. There is an online service program to provide convenience and efficiency from the presence of a third party in civil registration administration, Researcher want to know the purpose of the program, namely the chocolate program, namely. online system without queues, and get the order of community management and candysweet programs, namely. an online management program that can be managed anywhere online via websites and applications. Population and Civil Registration Service as an administrative service agency for population registration. This research using SEM-PLS is quantitative research with a sample size of 100 people using the structural equation model method. The empirical conclusions obtained show that the chocolate program's online service quality has a positive and significant effect on community satisfaction, the Permenmanis program's online service quality has a positive and significant influence on community satisfaction. People who do not understand technology well will have an impact of dissatisfaction, while there are often problems with website maintenance and management, giving rise to public complaints demanding better system improvements, so that the efficiency of updating data in the population system is easier, and the data available to the public is up to date. .. Keywords: Online Service Quality Program, Community Satisfaction